The role of attention in a joint-action effect. - Silviya P Doneva (Public Library of Science (PLoS), 2014)
The most common explanation for joint-action effects has been the action co-representation account in which observation of another's action is represented within one's own action system. However, recent evidence has shown that the most prominent of these joint-action effects (i.e., the Social Simon effect), can occur when no co-actor is present. In the current work we examined whether another joint-action phenomenon (a movement congruency effect) can be induced when a participant performs their part of the task with a different effector to that of their co-actor and when a co-actor's action is replaced by an attention-capturing luminance signal. Contrary to what is predicted by the action co-representation account, results show that the basic movement congruency effect occurred in both situations. These findings challenge the action co-representation account of this particular effect and suggest instead that it is driven by bottom-up mechanisms.